2017
DOI: 10.4236/jbm.2017.58005
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Human Chorionic Gonadotropin Levels among Pregnant Women with Morning Sickness Attending Antenatal Care Services at Ishaka Adventist Hospital, Uganda

Abstract: Globally, 50% -90% of pregnant women are affected by morning sickness of pregnancy, especially during the first trimester. Therefore this study was carried out to establish if there is association between urinary hCG levels and severity of nausea, retching and vomiting among pregnant women attending antenatal care (ANC) services at Ishaka Adventist Hospital (IAH). It was a quantitative cross-sectional study in which a pre-tested and standardized questionnaire with a mixture of both open and closed ended questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…Our results are supported by another study in which no significantlinkage between physiological characteristics (age and weight) of respondents and HCG level 16 .…”
Section: This Prospective Study Was Done In El Husseinsupporting
confidence: 89%
“…Our results are supported by another study in which no significantlinkage between physiological characteristics (age and weight) of respondents and HCG level 16 .…”
Section: This Prospective Study Was Done In El Husseinsupporting
confidence: 89%
“…Also in the study that sought to investigate the relationship between interval of membrane rupture and risk of neonatal septicemia, findings showed that the probability of neonatal septicemia increases independently and linearly with duration of membrane rupture up to 36 hours with 1.29 times more chance per 6 hours increase in membrane rupture duration before onset of labor [16][24-8] On the neonatal factors the researcher found out that birth weight had a significant influence on the occurrence of neonatal septicemia among babies admitted in pediatric ward of Kampala international university teaching hospital. This was in agreement with [17]in study that sought to examine risk factors for neonatal septicemia and perinatal death among infants enrolled on the prevention of prenatal sepsis trial in Soweto, South Africa and found out that low birth weight, first birth, emergency caesarean section and male sex were significantly associated with late or early onset of septicemia [29][30][31][32]. Also, [11] added that low birth weight is associated with an increased risk of neonatal septicemia among neonates.…”
Section: Discussionsupporting
confidence: 78%
“…Male partners being present can reduce these delays. The role of the promptness with which these things are done in reducing maternal morbidity and mortality cannot be overemphasized [19][20][21][22] [5] The proportion of participants having discussions on their partner's maternal health issues with their health providers was also found to be low in this study. This was to be expected given the low proportion who accompanied their partners to the health facilities.…”
Section: Discussionmentioning
confidence: 96%